A high-strength PUR flat-pasting product for inorganic composite panels and a preparation method thereof

By using a specific proportion of polyester polyol and polyether polyol in PUR hot melt adhesive, combined with a combination of petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer, the problem of insufficient bonding strength of the existing PUR hot melt adhesive under high temperature, water immersion, hot and cold cycles is solved, and the adhesion, water resistance and high temperature resistance of the product are significantly improved.

CN115895560BActive Publication Date: 2025-04-04CONFAY ADHESIVE TECH (GUANGDONG) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211527202.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-04
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing PUR hot melt adhesive has insufficient bonding strength retention rate under high temperature, water immersion, hot and cold cycles, and has a low final viscosity.

Method used

The combination of 30 to 80 parts of thermoplastic resin, 15 to 60 parts of polyester polyol, 15 to 45 parts of polyether polyol, and 8 to 15 parts of isocyanate is adopted, especially the polyester polyol of Evonius 7360 and Evonius 7380 is selected, and the mass ratio of (0.5 to 2):1 is controlled, and the mass ratio of (1 to 3):1:1 is controlled by the use of petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer.

Benefits of technology

The adhesion and final peel strength of PUR flat-paste products to inorganic composite plates are significantly improved, water resistance and high temperature resistance are improved, and initial bonding strength and final bonding strength are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003973364550000061
    Figure BDA0003973364550000061
Patent Text Reader

Abstract

The present invention relates to the field of hot melt adhesive technology, in particular to the field of IPC C09J175, and further to a high-strength PUR flat-pasting product for inorganic composite panels and a preparation method thereof. The following raw materials are included by mass: 330 to 80 parts of thermoplastic resin, 15 to 60 parts of polyester polyol, 15 to 45 parts of polyether polyol, and 8 to 15 parts of isocyanate. The high-strength PUR flat-pasting product for inorganic composite panels prepared by the present invention has good wettability to inorganic composite panels, high initial adhesion strength and final adhesion strength, and is resistant to high temperatures and water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hot melt adhesives, in particular to the field of IPC C09J175, and further to a high-strength PUR flat-lamination product for an inorganic composite board and a preparation method thereof. Background Art

[0002] PUR (Polyurethane Reactive), the full name in Chinese, is moisture-curing reactive polyurethane hot melt adhesive. Its main component is isocyanate-terminated polyurethane prepolymer, and its molecular structure contains polar and chemically active urethane groups (-NHCOO-) or isocyanate groups (-NCO). It has excellent adhesion to materials such as wood, metal, glass, rubber, plastic, leather, fabric, and paper. PUR hot melt adhesive has been used in Europe and the United States for decades, and the technology is mature. To this day, it is still a better adhesive in many fields.

[0003] Chinese patent CN 112322248 A discloses a PUR hot melt adhesive for composite panels and a preparation method thereof. The raw materials include polyol polymer, polyisocyanate, thermoplastic resin, silane coupling agent, and other additives. Although the problem of increased initial adhesion but decreased final adhesion after adding thermoplastic resin can be improved, the final adhesion still needs to be improved.

[0004] Chinese patent CN 108997965 B discloses a reactive polyurethane hot melt adhesive and a preparation method thereof. The reactive polyurethane hot melt adhesive comprises raw materials including polyether polyol, polyester polyol, polyisocyanate, terminal hydroxyl acrylate carbonate copolymer resin, additives and catalysts for enhancing water resistance. However, the reactive polyurethane hot melt adhesive prepared by this technical solution has a good bonding strength retention rate under high temperature, immersion in water, and hot and cold cycles, but its bonding strength needs to be improved. Summary of the invention

[0005] The first aspect of the present invention provides a high-strength PUR flat-laid product for an inorganic composite board, which comprises the following raw materials, by mass: 30 to 80 parts of thermoplastic resin, 15 to 60 parts of polyester polyol, 15 to 45 parts of polyether polyol, and 8 to 15 parts of isocyanate.

[0006] In some preferred embodiments, the polyester polyol has a hydroxyl value of 20 to 50 mgKOH / g and a number average molecular weight of 2000 to 5000 g / mol.

[0007] Preferably, the polyester polyol is a crystalline polyester polyol.

[0008] In some preferred embodiments, the crystalline polyester polyol is selected from one or more combinations of Evonik 7345, Evonik 7360, Evonik 7380, Evonik 7381, Evonik 7330, and Evonik 7340.

[0009] Preferably, the polyester polyol is selected from the combination of Evonik 7360 and Evonik 7380, and the mass ratio of Evonik 7360 and Evonik 7380 is (0.5-2):1. The applicant found that when the crystalline polyester polyol is selected from the combination of Evonik 7360 and Evonik 7380, especially when the mass ratio is (0.5-2):1, the prepared PUR flat product has good bonding strength; the applicant speculates that the use of Evonik 7360 and Evonik 7380 at this mass ratio makes the PUR flat product have better wettability to the inorganic composite board, thereby improving the adhesion to the inorganic composite board and improving its final peel strength.

[0010] When only polyester polyol is introduced into the system, the water resistance of the PUR flat product is poor because the ester group in the polyester polyol is easily hydrolyzed. In order to improve the water resistance of the PUR flat product, polyether polyol is introduced into the system of the present invention.

[0011] In some preferred embodiments, the polyether polyol has a hydroxyl value of 56 to 240 and a number average molecular weight of 600 to 2000.

[0012] Preferably, the polyether polyol has a hydroxyl value of 112 and a number average molecular weight of 1000.

[0013] In some preferred embodiments, the thermoplastic resin is selected from one or more combinations of petroleum resin, polyurethane elastomer, acrylic resin, ethylene vinyl acetate copolymer, and rosin resin.

[0014] In some preferred embodiments, the thermoplastic resin is selected from a combination of petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer.

[0015] The applicant has found that when the thermoplastic resin in the system is a polyurethane elastomer, the final bonding strength of the PUR product can be improved, but the initial bonding force of the PUR flat product is low, and it will cause the melt viscosity of the PUR flat product to be too large and the open time to be short; when a polyurethane elastomer and a petroleum resin are added to the system, the PUR product can have a higher final bonding strength while improving the high temperature resistance of the PUR flat product.

[0016] In some preferred embodiments, the petroleum resin has a softening point of 80-160° C. and a chromaticity of 2-6.

[0017] In some preferred embodiments, the petroleum resin is selected from C5 petroleum resin and / or C9 petroleum resin.

[0018] Preferably, the petroleum resin is C9 petroleum resin.

[0019] In order to ensure that the PUR flat product has excellent high temperature resistance and high final bonding strength, preferably, the softening point of the C9 petroleum resin is 80 to 120°C and the chromaticity is 3 to 5. The higher the softening point of the petroleum resin, the stronger the cohesive strength of the resin and the higher the final bonding strength, but too high a softening point will increase the melt viscosity of the PUR flat product and reduce the wetting ability of the PUR flat product, which is not conducive to the bonding of the PUR flat product.

[0020] In order to improve the initial adhesion of PUR flat products, ethylene vinyl acetate copolymer is introduced into the system of the present invention. The polar acetate groups contained in the ethylene vinyl acetate copolymer will form hydrogen bonds with the carbamate groups, urea groups, etc. in the system. The physical crosslinking degree of the PUR flat product after final curing will increase, and the cohesive strength will increase, thereby further improving the initial bonding strength of the PUR flat product. However, due to the poor compatibility of ethylene vinyl acetate copolymer with the polyurethane system, the melt viscosity of the system also increases significantly, which will affect the sizing process of the PUR flat product and may cause the final bonding strength of the PUR flat product after curing to decrease.

[0021] In order to solve the above problems, preferably, the vinyl acetate content of the ethylene vinyl acetate copolymer is 20-40wt%; preferably, the mass ratio of the petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer is (1-3): 1: 1. On the one hand, a higher vinyl acetate content can improve its compatibility with the system, and on the other hand, the compatibility of the petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer in the system under this mass ratio is optimal, thereby improving the comprehensive performance of the PUR product.

[0022] In some preferred embodiments, the isocyanate is any one of TDI (toluene diisocyanate), MDI (diphenylmethane diisocyanate), and IPDI (isophorone diisocyanate).

[0023] Another aspect of the present invention provides a method for preparing a high-strength PUR flat-laid product for an inorganic composite board, comprising the following steps:

[0024] (1) According to parts by mass, polyether polyol, polyester polyol and thermoplastic resin are uniformly mixed at 160-180° C. to completely dissolve them, and then dehydrated after keeping the mixture at the temperature for 1-3 hours.

[0025] (2) When the temperature drops to 70-90°C, add isocyanate and react at 100-120°C for 1-3 hours to obtain the product.

[0026] Beneficial effects:

[0027] 1. The polyester polyol of the present invention is selected from the combination of Evonik 7360 and Evonik 7380, and the mass ratio of Evonik 7360 and Evonik 7380 is controlled to be (0.5-2):1, so that the wettability of the PUR flat-laid product to the inorganic composite board is better, thereby improving the adhesion to the inorganic composite board and improving its final bonding strength.

[0028] 2. The present invention introduces a polyether polyol with a hydroxyl value of 112 and a number average molecular weight of 1000, which improves the problem of poor water resistance of PUR flat products due to the easy hydrolysis of the ester group in the polyester polyol.

[0029] 3. The present invention selects C9 petroleum resin with a softening point of 80-120°C and a chromaticity of 3-5, which ensures that the PUR flat-pasted product has excellent high temperature resistance and high final bonding strength.

[0030] 4. The present invention selects ethylene vinyl acetate copolymer with a vinyl acetate content of 20 to 40 wt%, which has good compatibility with the system and improves the initial bonding strength of the PUR flat-stick product.

[0031] 5. The present invention selects petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer to work together, and controls the mass ratio of petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer to be (1-3):1:1, so that the PUR flat-fitting product has excellent comprehensive performance. DETAILED DESCRIPTION

[0032] Example 1

[0033] Example 1 provides a high-strength PUR flat-laid product for an inorganic composite board, which comprises the following raw materials, in parts by mass: 60 parts of thermoplastic resin, 40 parts of polyester polyol, 25 parts of polyether polyol, and 10 parts of isocyanate.

[0034] The thermoplastic resin is C9 petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer; the mass ratio of the petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer is 2:1:1.

[0035] The C9 petroleum resin has a softening point of 110° C. and a chromaticity of 4 and is purchased from Kolon Industries, model number: HIKOTACK P-110S.

[0036] The polyurethane elastomer is DuPont Hytrel 3078.

[0037] The ethylene content of the ethylene vinyl acetate copolymer is 28 wt %, and the ethylene vinyl acetate copolymer is Escorene Ultra UL 40028CC.

[0038] The polyester polyols are Evonik 7360 and Evonik 7380, with a mass ratio of 1:1.

[0039] The polyether polyol is Dow VORANOL 1000LM.

[0040] The isocyanate is MDI (diphenylmethane diisocyanate).

[0041] A method for preparing a high-strength PUR flat-pasted product for an inorganic composite board comprises the following steps:

[0042] (1) According to parts by mass, polyether polyol, polyester polyol, ethylene vinyl acetate copolymer, polyurethane elastomer and C9 petroleum resin were mixed uniformly at 170° C. to completely dissolve, and then dehydrated after keeping the mixture at the temperature for 2 hours.

[0043] (2) When the temperature drops to 80°C, add isocyanate and react at 110°C for 2 hours to obtain the product.

[0044] Example 2

[0045] Example 2 provides a high-strength PUR flat-laid product for an inorganic composite board, which comprises the following raw materials, in parts by mass: 70 parts of thermoplastic resin, 50 parts of polyester polyol, 30 parts of polyether polyol, and 15 parts of isocyanate.

[0046] The thermoplastic resin is C9 petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer; the mass ratio of the petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer is 2:1:1.

[0047] The C9 petroleum resin has a softening point of 110° C. and a chromaticity of 4 and is purchased from Kolon Industries, model number: HIKOTACK P-110S.

[0048] The polyurethane elastomer is DuPont Hytrel 3078.

[0049] The vinyl acetate content of the ethylene vinyl acetate copolymer is 28 wt %, and the ethylene vinyl acetate copolymer is Escorene Ultra UL 40028CC.

[0050] The polyester polyols are Evonik 7360 and Evonik 7380, with a mass ratio of 1:1.

[0051] The polyether polyol is Dow VORANOL 1000LM.

[0052] The isocyanate is MDI (diphenylmethane diisocyanate).

[0053] A method for preparing a high-strength PUR flat-pasted product for an inorganic composite board comprises the following steps:

[0054] (1) According to parts by mass, polyether polyol, polyester polyol, ethylene vinyl acetate copolymer, polyurethane elastomer and C9 petroleum resin were mixed uniformly at 170° C. to completely dissolve, and then dehydrated after keeping the mixture at the temperature for 2 hours.

[0055] (2) When the temperature drops to 80°C, add isocyanate and react at 110°C for 2 hours to obtain the product.

[0056] Example 3

[0057] Example 3 provides a high-strength PUR flat-ply product for an inorganic composite board, and its specific implementation is the same as that of Example 2, except that the polyester polyol is selected from Evonik 7362 and Evonik 7360, with a mass ratio of 1:1.

[0058] Example 4

[0059] Example 4 provides a high-strength PUR flat-laid product for an inorganic composite board, and its specific implementation is the same as that of Example 2, except that the mass ratio of Evonik 7360 to Evonik 7380 is 3:1.

[0060] Example 5

[0061] Example 5 provides a high-strength PUR flat-laid product for an inorganic composite board, and its specific implementation is the same as that of Example 2, except that the thermoplastic resin is a polyurethane elastomer.

[0062] Example 6

[0063] Example 6 provides a high-strength PUR flat-laid product for an inorganic composite board, and its specific implementation is the same as that of Example 2, except that the C9 petroleum resin has a softening point of 145° C. and a chromaticity of 4, and is purchased from Kolon Industries, model: HIKOTACK P-140.

[0064] Example 7

[0065] Example 7 provides a high-strength PUR flat-laid product for an inorganic composite board. The specific implementation manner is the same as that of Example 2, except that the vinyl acetate content of the ethylene-vinyl acetate copolymer is 14 wt %, and the ethylene-vinyl acetate copolymer is Escorene Ultra FL 00714.

[0066] Example 8

[0067] Example 8 provides a high-strength PUR flat-ply product for an inorganic composite board, and its specific implementation is the same as that of Example 2, except that the mass ratio of the petroleum resin, the polyurethane elastomer and the ethylene-vinyl acetate copolymer is 2:1:2.

[0068] Performance Testing

[0069] The PUR flat-stick products prepared in Examples 1 to 8 were used to bond two standard bonding substrates, with a coating amount of 40 g / m 2 After bonding, it is cured at 25°C and 50% RH, and the complete curing time is 24 hours.

[0070] The substrate was tested as follows:

[0071] 1. Initial adhesive strength: Curing for 3 minutes at 25°C and 50% RH, measured in accordance with standard GB / T7124-2008.

[0072] 2. Final adhesive strength: Curing was carried out at 25°C and 50% RH for 24 hours and measured in accordance with the standard GB / T 7124-2008.

[0073] 3. High temperature resistance: Heat treat the cured substrate at 150°C in a blast drying oven for 3 hours. After cooling, test the bonding strength again and calculate the bonding strength retention rate in %.

[0074] 4. Water resistance: Soak the cured substrate in 50℃ water for 1 hour and observe whether the substrate falls off. If it does not fall off, it is qualified; if it falls off, it is unqualified.

[0075] Test Results

[0076] Table 1:

[0077]

Claims

1. A high-strength PUR flat-pasted product for inorganic composite panels, characterized in that: The following raw materials are included by weight: 30 to 80 parts of thermoplastic resin, 15 to 60 parts of polyester polyol, 15 to 45 parts of polyether polyol, and 8 to 15 parts of isocyanate; The thermoplastic resin is selected from a combination of petroleum resin, polyurethane elastomer and ethylene vinyl acetate copolymer; The petroleum resin is C9 petroleum resin, the softening point of the C9 petroleum resin is 80-120° C., and the chromaticity is 3-5; The vinyl acetate content of the ethylene vinyl acetate copolymer is 20 to 40 wt %; The mass ratio of the petroleum resin, the polyurethane elastomer and the ethylene vinyl acetate copolymer is (1-3):1:1; The polyester polyol is selected from a combination of Evonik 7360 and Evonik 7380, and the mass ratio of Evonik 7360 to Evonik 7380 is (0.5-2):

1.

2. The high-strength PUR flat-pasted product for inorganic composite panels according to claim 1, characterized in that: The polyether polyol has a hydroxyl value of 56 to 240 and a number average molecular weight of 600 to 2000.

3. A method for preparing a high-strength PUR flat-pasted product for an inorganic composite board according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) According to parts by mass, polyether polyol, polyester polyol and thermoplastic resin are uniformly mixed at 160-180° C. to completely dissolve them, and then dehydrated after keeping the mixture at the temperature for 1-3 hours; (2) When the temperature drops to 70-90°C, add isocyanate and react at 100-120°C for 1-3 hours to obtain the product.

Citation Information

Patent Citations

  • A reactive polyurethane hot melt adhesive and its preparation method

    CN108997965B

  • PUR hot melt adhesive for composite board and preparation method of PUR hot melt adhesive

    CN112322248A

  • Pressure maintaining-free PUR hot-melt adhesive and preparation method thereof

    CN108285766A